Mediating effect of meaningful work on the influence of job resources, personal resources and transformational leadership towards work engagement - Zakaria, Zaki (2019)
Having engaged workers are necessary to lead the way for the betterment of employees’ and organizational performances. This is possible as engaged employees perform their duties with full of energy, passion and dedication. However, studies conducted worldwide revealed that majority of employees are falling under unengaged group. The same scenario happens among Malaysian employees. Thus, the main objective of this study is to determine the mediating effect of meaningful work on the influence of job resources, personal resources and transformational leadership towards work engagement among employees in Public Service Department of Malaysia (PSDM). In this study, a research framework is being developed based on the combination of Job Demands-Resources (JD-R) model, Khan’s Theory of Psychological Condition of Engagement (KTPCE) and Transformational Leadership Style. Based on these theories, this study was conducted to determine whether job resources, personal resources and transformational leadership have significant influence on work engagement in the presence of meaningful work as the mediator. This study adopted quantitative research paradigm in which data were collected from 364 respondents at Public Service Department of Malaysia (PSDM). The two identified working groups are Management & Professional Group and Implementer Group. In meeting all the five objectives of this study, a cross-sectional survey design was employed. The sample of this study was chosen by using proportionate stratified random sampling technique. Data was analysed using descriptive statistics and Structural Equation Modeling (SEM) using Analysis of Moment Structures (AMOS). The descriptive finding in answering objective one and two of the study confirmed that majority of employees at PSDM possessed high level of work engagement, meaningful work, personal resources and transformational leadership. Only job resources have reported moderate level. In answering objective three, four and five, SEM-AMOS analysis is being applied. For objective three, the result confirmed that personal resources and meaningful work have significant influence on work engagement. However, job resources and transformational leadership revealed non-significant result. In answering objective four, the result mentioned that job resources and personal resources have significant influence on meaningful work. However, transformational leadership produced nonsignificant result. For objective five, the mediating effect of meaningful work was tested using the bootstrapping technique. The result of the analysis indicated that meaningful work did mediate the influence of job resources and personal resources towards work engagement. Nevertheless, meaningful work did not mediate the influence of transformational leadership on work engagement. In conclusion, this study concluded that personal resources and meaningful work has direct influence towards work engagement. Meanwhile, job resources have indirect effect towards work engagement through meaningful work. On the other hand, transformational leadership reported non-significant influence towards work engagement in both direct relationship and mediation study. This study contributed to the body of knowledge in terms of developing research framework from the context of public service in Malaysia. It also enriches the knowledge of meaningful work as mediator which is important from academic and public service perspective. More importantly, this study supports that both JD-R model and KTPCE theory are vital in increasing the level of work engagement among employees at PSDM. In addition, this study also highlighted the implications and recommendations for human resource development practitioners towards increasing the level of work engagement among employees in public service in Malaysia.